Acute phase response in familial Mediterranean fever - Korkmaz, C; Özdogan, H; Kasapçopur, Ö; Yazici, H (Annals of the rheumatic diseases, 2002)
Objective: To test the hypothesis that not all acute phase reactants respond in the same way during attacks of familial Mediterranean fever (FMF) and that there is a subclinical acute phase response (APR) in a proportion of patients during the interval between attacks. Methods: Blood and urine samples were obtained from 49 patients with FMF during an attack and the attack-free period that followed, to test for erythrocyte sedimentation rate, C reactive protein (CRP), fibrinogen, white blood cell count, platelet count, factor VIII related antigen, haptoglobin, protein electrophoresis, ferritin, proteinuria, and haematuria. Control groups comprised 29 patients with juvenile idiopathic arthritis, 10 patients with various infectious diseases, and 19 healthy subjects. Results: A marked APR was seen during the FMF attacks which was comparable with that obtained in the diseased control groups. CRP was the only acute phase protein that was raised during all attacks. Neither thrombocytosis nor an increase in ferritin levels (except one) was noted in any attack. Serum albumin levels remained unchanged. In two thirds of the patients with FMF a continuing APR was seen in between the attacks. Conclusion: Platelet, ferritin, and albumin responses are not part of the significant APR seen during short lived attacks of FMF, and inflammation continues in about two thirds of the patients during an attack-free period.